2003
DOI: 10.1159/000069486
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prognostic Significance of Early Elevated Serum Uric Acid Levels in Low Birthweight Infants

Abstract: This study examined the utility of serum uric acid concentrations in the first day of life to identify infants with severe brain injury (grade III or IV intraventricular hemorrhage and/or periventricular leukomalacia). The serum uric acid concentrations in infants with severe brain injury were compared to those without. Severe brain injury was assessed in 151 infants with birthweight ≤1,251 g admitted before 24 h of life. The risk of severe brain injury was related to 5-min Apgar scores (odds ratio 0.79, CI 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In support of these findings, Aliefendioglu et al (2006) found that high UA concentrations in CSF were associated with a higher risk of IVH. However, other study of low birth weight infants did not find association between elevated UA in serum and IVH (Sysyn and Rozycki, 2003). UA has conflicting results as brain injury biomarker.…”
Section: Biomarkers Of Intraventricular Hemorrhagementioning
confidence: 81%
“…In support of these findings, Aliefendioglu et al (2006) found that high UA concentrations in CSF were associated with a higher risk of IVH. However, other study of low birth weight infants did not find association between elevated UA in serum and IVH (Sysyn and Rozycki, 2003). UA has conflicting results as brain injury biomarker.…”
Section: Biomarkers Of Intraventricular Hemorrhagementioning
confidence: 81%
“…UA has also been studied as a biomarker for brain injury in prematurity. Perlman and Risser (1998) reported increased UA concentrations on the first postnatal day of life in preterm infants who developed IVH, although Sysyn and Rozycki (2003) failed to demonstrate a statistically significant correlation between UA and IVH in preterm infants.…”
Section: Intraventricular Hemorrhagementioning
confidence: 96%
“…On the other hand, the relationship between plasma UA and the development of severe IVH or PVL in preterm neonates is controversial. Pearlman et al reported increased UA concentrations on the first postnatal day in ELBW infants developing severe IVH/PVL, even after adjustment for GA and other relevant clinical variables [ 105 ]; subsequent data from a larger sample of preterm neonates with similar brain injury, however, failed to confirm this association [ 106 , 107 ]. Finally, significantly higher UA levels were observed in the CSF of preterm neonates with IVH grade 2 to 4 [ 107 ].…”
Section: Free Radical Biomarkers In Neonatal Brain Injurymentioning
confidence: 99%